Maternal Psychological Distress and Parent-Reported Child Behavioural and Emotional Outcomes Among Mothers of Children with Autism Spectrum Disorder: A Cross-Sectional Study - Khulud Ahmad Rezq; Haia Mahdi Hindi Albalawi; Hanan F. Alharbi (Healthcare, 2026)
Background: Mothers of children with autism spectrum disorder (ASD) face numerous challenges in meeting their children’s needs. This study aimed to assess parent-reported child behavioural and emotional outcomes and the levels of anxiety, depression, and stress among mothers of children with ASD. It also explored the correlations between parent-reported child behavioural and emotional outcomes and maternal mental health, as well as potential factors associated with these outcomes. Methods: A cross-sectional study was conducted between 30 December 2022 and 23 March 2023. An online questionnaire was distributed through autism associations across Saudi Arabia. The survey included (1) demographic data; (2) the Autism Family Experience Questionnaire (AFEQ) for children’s behavioural and emotional outcomes; and (3) the Depression, Anxiety, and Stress Scale-21 (DASS-21). Statistical analyses were performed using Jamovi software. Results: The study included 218 mothers of children with ASD. Extremely severe anxiety was reported by 41.3% of mothers, while 30.7% had normal stress and 30.7% had normal depression scores. The mean AFEQ symptom score was 37.4 ± 5.02. Univariate analysis revealed significant associations between parent-reported child behavioural and emotional outcomes and maternal mental health. In the multivariate analysis, higher family income (5000–10,000 SAR, p < 0.001; >10,000 SAR, p = 0.009) was associated with more favourable outcomes, while having more than one child with ASD was associated with less favourable outcomes (p = 0.015). Anxiety was positively associated with having two (p = 0.003) or three children (p = 0.029), while depression was negatively associated with having more than three children (p = 0.001). Conclusions: Higher family income was associated with more favourable parent-reported child behavioural and emotional outcomes, whereas having more than one child with ASD was associated with less favourable outcomes and higher maternal anxiety.